Can AI Predict Drug-Drug Interactions? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2019)
Drug-drug interactions (DDIs) are a major concern in healthcare, as they can lead to adverse drug reactions (ADRs), reduced treatment efficacy, and even life...
Keywords: Drug Discovery and Pharmaceutical AI; Predict; Drug-Drug; Interactions; Artificial Intelligence; Machine Learning; Deep Learning